Influence of agarose on the electrochemical behaviour of the silver and platinum aqueous acid electrolyte interface - Pasquale, Miguel Ángel (2003)
The influence of agarose on the electrochemical behaviour of the interfaces silver/aqueous agarose + 0.014 M silver sulfate + 0.5 M sodium sulfate + 0.01 M sulfuric acid and platinum/aqueous agarose + 0.5 M sulfuric acid, at 298 K, was studied. Freshly prepared and aged agarose-containing solutions in the range of agarose concentration 0.01 ≤ caga ≤ 0.5% w/v were used. Viscosity, open circuit potential, solid sample infrared spectra and conventional voltammetric measurements were performed. The electrooxidation of adsorbates produced from both the homogeneous and heterogeneous decomposition of agarose-containing solutions on platinum was investigated. Results are discussed in terms of the structure and interactions of agarose molecules in sols and gels. The electrooxidation of adsorbed residues can be explained within the complex reaction pathway for the electrooxidation of saccharides previously discussed in the literature.